Can community and educational interventions designed from the ground-up promote social and emotional learning? Experimental and quasi-experimental impacts of a country-wide Portuguese initiative - Barata, M. Clara; Alexandre, Joana; Castro, Catarina; Colaço, Carla (Frontiers in Education, 2024)
Introduction: Social and emotional learning (SEL) is a powerful predictor of several outcomes throughout life, such as relationships, citizenship behavior, academic and job performance, and mental and physical health. The Portuguese Gulbenkian Academies for Knowledge supported the implementation and rigorous impact assessment of community and educational interventions aiming to promote SEL in participants 0 and 25 years of age.Methods: This paper presents a secondary-data analysis of the experimental and quasi-experimental impacts of 40 Academies on the OECD Survey of Social and Emotional Skills. Eight Academies (N=4,460 participants) implemented an experimental approach, while 32 Academies (N=14,274 participants) employed a quasi-experimental approach.Results: We found experimental and quasi-experimental evidence of significant positive results of the Academies for various skills, and consistent impacts from the perspective of child/youth participants and teachers, particularly for Curiosity and Assertiveness. Effect sizes were small.The impact evaluation of the Gulbenkian Academies for Knowledge has the potential to support considerable changes in the field of SEL interventions, nationally and internationally, by informing discussion of evidence-based SEL interventions, and offering a sustainable model of capacity building with long-lasting effect on practices of SEL professionals.